PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA KELAS V SDN 1 GODONG - Rofiatus Sanabila; A. Y. Soegeng Ysh; Joko Sulianto (STKIP Subang, 2022)
The background that drives this research is that students have difficulty understanding science material, lack of students' understanding of science material, learning activities have not used effective learning models, and student learning outcomes have not been maximized. The problem in this study is whether there is an effect of the problem based learning model on the learning outcomes of science class V SDN 1 Godong?. The purpose of this study was to determine the effect of the problem based learning model on the learning outcomes of fifth grade science students at SDN 1 Godong. This study uses a quantitative method with a pre-experimental design in the form of a one-group pretest-posttest design. Data collection techniques in this study through interviews, observations, tests, and documentation. The results showed that the average pretest was 46.8 and the average posttest was 87.9. Based on the paired sample t-test with df = N-1 = 32-1 = 31 with a significant level of 0.05, it was obtained tcount = 14,442 ttable = 2,039. From the results of these calculations obtained tcount > ttable, it can be concluded that there is a difference and mastery of learning from the problem based learning model on the learning outcomes of science class V SDN 1 Godong. Based on the research results obtained, the authors suggest that the application of the problem based learning model can be developed into an effective and fun learning activity.